Effect of vinyl acetate effluent in reducing heat of hydration of concrete - Ismail, Mohammad (Springer Verlag, 2016)
Waste generation especially in surface coating industries is a potential pollutant to the environment globally. Waste disposal in the form of recycling or reused has gained some recognition as a raw material in many kind of interested fields. This study is therefore, aimed at utilizing Vinyl acetate effluent generated from manufacturing process of paint as polymer modifier in concrete. The research highlights the influence of Vinyl acetate effluent on setting time and control of heat of hydration in concrete. Three specimens containing 0%, 2.5% and 5% of Vinyl acetate effluent by weight of cement were prepared in cubic moulds. The temperature rises due to heat of hydration in all mixes were recorded. Finding shows that incorporating Vinyl acetate effluent considerably delayed the setting time in cement paste and reduced the total temperature rise in polymer modified concrete. Therefore, addition of Vinyl acetate effluent polymer in concrete may improve the properties of concrete to some extent particularly in mass concrete production.